Female Attitudes Towards Self-employment and Breaking Occupational Stereotypes in Jharkhand. Issue 2 (December 2019) - Mahato, Madhuri; Vardhan, Julie
Although in recent times a growing number of women are entering into occupations that were traditionally dominated by men, these gains have not been equally realized. In the state of Jharkhand, a group of women have broken the occupational stereotypes and have become auto drivers, of vehicles that have suitably been named Pink Autos. An empirical study was undertaken to explore the intrinsic as well as extrinsic factors that have affected their occupational choice to break the stereotype. The results provide insights into the driving factors for the success for women micro-entrepreneurs.